Doing Experimental Media Archaeology Theory - Fickers, Andreas (De Gruyter, 2022)
The volume aims at taking the materiality of past media devices seriously and explores the heuristic possibilities of an experimental study of these devices. It offers a sophisticated reflection on the epistemological and heuristic potential of hands-on media historical research.